Use of End-of-Class Quizzes to Promote Pharmacy Student Self-Reflection, Motivate Students to Improve Study Habits, and to Improve Performance on Summative Examinations - Ruth Vinall; Eugene Kreys (MDPI AG, 2020)
Underperforming students are often unaware of deficiencies requiring improvement until after poor performance on summative exams. The goal of the current study was to determine whether inclusion of individual end-of-class formative quizzes, which comprise of higher level Bloom's questions, could encourage students to reflect on and address deficiencies and improve academic performance. Ninety-seven out of 123 first-year pharmacy students (79%) enrolled in a Biochemistry and Cell & Molecular Biology course participated in a single-blinded, randomized, controlled, crossover study. Paired t-test analyses demonstrated that that implementation of individual end-of-class formative quizzes resulted in significantly higher summative exam scores for below average students (p = 0.029). Notably, inclusion of quizzes significantly improved performance on higher Bloom's questions for these students (p = 0.006). Analysis of surveys completed by students prior to summative exam indicate that the formative end-of-class quizzes helped students identify deficiencies (89%) and making them feel compelled to study more (83%) and attend review sessions (61%). Many students indicated that quizzes increased stress levels (45%). Our collective data indicate that quizzes can improve summative exam performance for below average first year pharmacy students, and improve self-reflection and student motivation to study. However, the impact on student stress levels should be considered.